2015
DOI: 10.18865/ed.25.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use, Incident Dementia and Alzheimer Disease in Elderly African Americans

Abstract: Objective: To investigate the association between statin use, incident dementia, and Alzheimer disease (AD) in a prospective elderly African American cohort. Design:Two stage design with a screening interview followed by a comprehensive in-home assessment conducted over an eight-year period. Diagnoses of incident AD and dementia were made by consensus. Statin use was collected at each evaluation. Measurements of low-density lipoprotein cholesterol (LDL), C-reactive protein (CRP) and APOE genotype were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Eight studies [2123,33,35,46,51,52] reported adjusted ORs instead of HRs (11,336 participants and 1,001 stroke events). The pooled estimate indicated increased odds of incident dementia in those with prevalent stroke compared to no prevalent stroke (pooled OR = 1.53, 95% CI: 1.30–1.80, p<0.00001, I 2 = 0%; 95% PI: 1.22 – 1.84; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [2123,33,35,46,51,52] reported adjusted ORs instead of HRs (11,336 participants and 1,001 stroke events). The pooled estimate indicated increased odds of incident dementia in those with prevalent stroke compared to no prevalent stroke (pooled OR = 1.53, 95% CI: 1.30–1.80, p<0.00001, I 2 = 0%; 95% PI: 1.22 – 1.84; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A small number of studies have examined statins and cognitive dysfunction,3,13 with few specifically examining this association in CAD patients as a primary outcome 28. Because high-dose statins are often prescribed in CAD,29 the potential risk of low LDL levels on cognition are of particular concern.…”
Section: Introductionmentioning
confidence: 99%
“…Seven cohort studies Chuang, Lin, Lin, Sung, & Kao, 2015;Hendrie et al, 2015;Hippisley-Cox & Coupland, 2010;Li et al, 2010;Yang et al, 2015) and five case control studies (Booker et al, 2016;Chen, Liu, Chen, & Wu, 2014;Corrao et al, 2013;Horsdal et al, 2009;Lin et al, 2015) found that statin use was associated with a reduced risk of dementia. According to these studies, beginning treatment with high doses of lipophilic statins before an early old age (<80 years old) and taking these statins for a long time might reduce the risk of dementia.…”
Section: Statinsmentioning
confidence: 99%